EFFECTS OF SELENIUM FORTIFICATION ON THE MINERAL AND FATTY ACID PROPERTIES OF PLEUROTUS OSTREATUS JACQ - OYETAYO VO; FADUGBA AE; ARIYO OO (Innovare Journal of Food Sciences, 2023)
Objective: Mineral elements are very important in physiological processes and hence affect the quantity and types of metabolites produced by plants and animals. In this study, the effect of selenium fortification on the mineral and fatty acid contents of Pleurotus ostreatus was investigated. Methods: P. ostreatus was cultivated on substrate enriched with sodium selenite. The mineral and fatty acid content of the selenium-enriched and non-selenium-enriched fruit bodies were analyzed using standard methods. Results: Data revealed that fortification of P. ostreatus results to increase in the values of Ca, Mg, and Se while the value of Zn reduced. A total of 13 and 18 peaks were, respectively, observed in the chromatograms of non-selenium-fortified and selenium-fortified P. ostreatus. The following fatty acids pentadecanoic acid, 13-hexyloxacyclotridec-10-en-2-one, oleic acid, n-hexadecanoic acid, stearic acid, undecylenic acid, 10-undecenoyl chloride, and pentadecanoic acid 2-hydroxy-1- (hydroxymethyl)ethyl were common to both selenium-fortified and non-fortified P. ostreatus. Conclusion: In conclusion, fortification of P. ostreatus markedly affects the mineral and fatty acids of its fruit bodies with more fatty acids present in P. ostreatus fortified with selenium.